Srilankan Tourism (SLT): A Forecast of Foreign Tourists (FFT) - Ismail, M.B.M.; Velnampy, T.; Mustafa, A.M.M. (Global Journals Inc. (USA, 2012)
Tourism has become a popular global leisure activity. Srilankan tourism has beaches, Archeological Sites, National Parks, Elephants, Adventure Sports and Precious stone mining. Sri Lanka has 39 tourist attractions all over the island. The International media reports published about the improvements in tourism industry of January 2008 by 0.6%, March 2008 by 8.6% when comparing to last year's (2007) figures. The 2004 Indian Ocean Tsunami and the past civil war have reduced tourist arrivals but Sri Lanka received over half a million tourists in 2006. Number of tourists’ arrival was 559600 in the year 2006. From secondary data analysis and literature review, research problem exists on two important variables such as period (year) and tourist (number of tourists’ arrivals to Sri Lanka).
Keywords: Srilankan Tourism; Forecast